THE PHENOMENON OF COUNSELOR DOING COPY-PASTE IN DESIGNING GUIDANCE AND COUNSELING PROGRAMS - Zulfani Nurfarihah; Shofa Salsabila Aziza; Rahmawati Yuliani; Fadillah Lutfi Ramadhan; Mitha Ahya Dianty; Wulan Winda Purnama (Study Program Guidance and Counseling, Univesitas Pendidik, 2022)
In providing counseling guidance services, a counselor or guidance and counseling teachers need to have good competence following the Regulation of the Minister of National Education of the Republic of Indonesia Number 27 Year 2008 on Academic Qualification Standards and Counselor Competency. In Indonesia, it is still found that some problems that faced by guidance and counseling teachers in the preparation of guidance and counseling programs, one of which is the guidance and counseling teacher who copied and pasted the counseling program last year. This article will explain an overview of the competence of guidance and counseling teachers in designing guidance and counseling programs, challenges in designing guidance and counseling programs, the factors that caused copy-pasting the guidance and counseling programs, and the efforts to improve the professional competence. This study uses a literature review method. The study revealed that a general overview of the competence of guidance and counseling teachers in designing guidance and counseling programs is in the high and medium categories. There are various challenges in designing guidance and counseling programs: 1) guidance and counseling teachers do not analyze every aspect of programming; 2) guidance and counseling teachers are lacking in making the equivalence of guidance and counseling service hours with subject hours; 3) guidance and counseling teachers do not receive special socialization and training on Pedoman Operasional Penyelenggaraan Bimbingan Konseling (POBK); 4) the guidance and counseling service programs do not receive support from school leaders in terms of financing. Efforts to improve professional competence in designing guidance and counseling programs are analyzing student needs, attending training, guidance and counseling workshops and seminars, implementing Continuous Professional Development (CPD), and following instructions from Ministerial Regulation Number 27 Year 2008 on Academic Qualification Standards and Counselor Competency in designing guidance and counseling programs.